2001
DOI: 10.1073/pnas.191384198
|View full text |Cite
|
Sign up to set email alerts
|

Fruiting body formation by Bacillus subtilis

Abstract: Spore formation by the bacterium Bacillus subtilis has long been studied as a model for cellular differentiation, but predominantly as a single cell. When analyzed within the context of highly structured, surface-associated communities (biofilms), spore formation was discovered to have heretofore unsuspected spatial organization. Initially, motile cells differentiated into aligned chains of attached cells that eventually produced aerial structures, or fruiting bodies, that served as preferential sites for spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

43
1,392
4
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 1,030 publications
(1,440 citation statements)
references
References 26 publications
43
1,392
4
1
Order By: Relevance
“…Strains were maintained in Lysogeny broth (LB) medium (LB-Lennox, Carl Roth; 10 g/L tryptone, 5 g/L yeast extract, and 5 g/L NaCl), while MSgg medium was used for biofilm induction (Branda et al 2001).…”
Section: Strains and Cultivation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strains were maintained in Lysogeny broth (LB) medium (LB-Lennox, Carl Roth; 10 g/L tryptone, 5 g/L yeast extract, and 5 g/L NaCl), while MSgg medium was used for biofilm induction (Branda et al 2001).…”
Section: Strains and Cultivation Conditionsmentioning
confidence: 99%
“…9, 2017; 5 diversification in biofilms of Gram-positive bacteria has not received much attention. Bacillus subtilis is a wide spread, plant growth promoting spore-former, known from its ability to form complex pellicle biofilms at the liquid-air interface (Branda et al 2001). Previous studies already indicated that this bacterium readily diversifies into distinct colony types when cultivated under static or planktonic conditions (Leiman et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, B. subtilis sporulation has traditionally been studied as an autonomous single-cell event. That unicellular focus changed, however, with the identification of two separate extracellular signals needed to initiate sporulation (Grossman & Losick, 1988) and the discovery that wild-type B. subtilis colonies contain morphologically distinct fruiting bodies where sporulation occurs (Branda et al, 2001). In addition to intercellular communication at the start of B. subtilis sporulation, another signaling system was discovered that controls programmed cell death of non-sporulating cells in the fruiting body at a later stage of the process (GonzalezPastor et al, 2003).…”
Section: Bacteria As Masters Of Cell-cell Interactionsmentioning
confidence: 99%
“…The resulting PCR product was cloned in frame with the carboxy-6xHis fusion at the NcoI and XhoI restriction sites of pET28a. The pksN and pksJ didomains were cloned in a similar fashion from the Bacillus subtilis strain NCIB 3610 (49). The pksJ-AT2 didomain was amplified using primers: Forward 5' AGCTAGCTTTGAACTGTGGGAAACAGA 3' and reverse 5' ACTCGAGTCATTTTTGCAATGTCCATAATCC 3'.…”
Section: Construction Of Jamc Pksj and Pksn Nrps Constructsmentioning
confidence: 99%